Peran Kecerdasan Emosional dan Spiritual terhadap Kinerja melalui Komitmen Afektif - Reza Athabi Zayeed (Penerbit Goodwood, 2025)
Purpose: Examine the influence of Emotional Intelligence and Spiritual Intelligence on BMT BIF Yogyakarta Employee Performance through Organizational Affective Commitment as a mediating variable. Methodology/approach: The method in this research is quantitative. Sample in this study was all BMT BIF employees who worked in 11 branch offices spread throughout DIY. The sampling method uses non-probability sampling. The data analysis technique uses Structural Equation Modeling (SEM) with the Smart PLS version 4 analysis tool. Results/findings: (1) Emotional Intelligence has a positive and significant effect on Employee Performance, (2) Spiritual Intelligence has a positive and significant effect on Performance. Employees, (3) Emotional Intelligence has no significant effect on Affective Commitment, (4) Spiritual Intelligence has a positive and significant effect on Affective Commitment, (5) Affective Commitment has no significant effect on Employee Performance, (6) Emotional Intelligence has no significant effect on Employee Performance through Affective Commitment as a mediating variable, (7) Spiritual Intelligence does not have a significant effect on Employee Performance through Affective Commitment as a mediating variable. Conclusion: Emotional intelligence variables have a positive and significant effect on employee performance when tested directly Limitations: The limitations of this research are that the number of samples is not too large and the research results are only based on respondents' answers via the questionnaire distributed Contribution: The contribution of this research is aimed at developing science around Human Resources and Organizational management.